Design and Debris : A Chaotics of Postmodern American Fiction - Conte, Joseph M. (Joseph Mark), 1960- (Book collections on Project MUSE., 2002)
Reading eight major contemporary authors through the lens of chaos theory, Conte offers new and original interpretations of works that have been the subject of much critical debate. Design and Debris discusses the relationship between order and disorder in the works of John Hawkes, Harry Mathews, John Barth, Gilbert Sorrentino, Robert Coover, Thomas Pynchon, Kathy Acker, and Don DeLillo. In analyzing their work, Joseph Conte brings to bear a unique approach adapted from scientific thought: chaos theory. His chief concern is illuminating those works whose narrative structures locate order hidden.